Secure large-scale bingo - Martinez-Balleste, A.; Sebe, F.; Domingo-Ferrer, J. (ITCC 2004 : International Conference on Information Technology: Coding and Computing : April 5-7, 2004, Las Vegas, Nevada : proceedings, 2004)
When designing a secure Internet version for keno or bingo for a large group of players, a multicast communication model is likely to be used for source-to-players communication. For a large group of players, this can potentially overwhelm the source, a problem which is known as implosion. We present a scheme for large-scale bingo which avoids implosion in the many-to-one communication between the players and the hall. The resulting scheme aggregates information using a probabilistic public-key additive privacy homomorphism and guarantees the security of communications.